Reactive Oxygen Species‐Mediated Pyroptosis with the Help of Nanotechnology: Prospects for Cancer Therapy. Issue 1 (8th December 2022) - Ding, Yuan; Ye, Binglin; Sun, Zhongquan; Mao, Zhengwei; Wang, Weilin
Abstract : Tumor resistance to apoptosis and the immunosuppressive tumor microenvironment are two main reasons for the poor outcomes of tumor treatment. Pyroptosis is a newly discovered form of programmed cell death, featuring surprising proinflammatory activity. Recent evidence shows that tumor cell pyroptosis leads to strong inflammatory responses and significant tumor regression, which is different from apoptotic cell death. Strategies based on different types of nanoparticles for pyroptosis induction have become a useful tool for tumor treatment. Reactive oxygen species (ROS) is considered an efficient way to cause pyroptosis, and ROS‐based nanotechnologies have been a powerful strategy for pyroptosis induction and cancer treatments. This review covers recent progress in ROS‐induced pyroptosis and nanotherapy to trigger ROS‐mediated pyroptosis in cancer. Abstract : Pyroptosis is a newly discovered programmed cell death which plays an important role in tumor therapy. Reactive oxygen species (ROS)‐based nanotechnologies able to induce pyroptosis have also been developed and have gained increasing interest. Herein, the important studies published in the last few years about the use of different ROS‐mediated nanotechnologies to trigger pyroptosis are summarized.